'A Caesar for our time': toward empathy and perspective-taking in new teachers' drama practices in diverse classrooms. Issue 2 (2nd April 2020) - Athanases, Steven Z.; Sanchez, Sergio L.
ABSTRACT: Within a partnership between a California university and Globe Education (Shakespeare's Globe, London), this study features early-career teachers working to infuse Shakespeare and drama in diverse K-12 classes. Teachers needed links between a five-day immersive London course and new jobs in diverse California schools. A three-day university Institute a year later provided a structural bridge, featuring unit designs and drama activities for Julius Caesar . Empathy and perspective-taking provided a conceptual/thematic bridge, making text and activities timely for democratic, equitable societies. Adaptive teaching provided a pedagogical bridge, guiding teachers to make partnership practices meaningful. Two first-year teacher cases illustrate challenges and possibilities.